Determinan Tingkat Kemiskinan Masyarakat di Provinsi Sumatera Utara: Peran Zakat sebagai Variabel Pemoderasi - Nasution, Faisal Umri; Suratno; Sailendra; Darmansyah (Jurnal Informatika Ekonomi Bisnis, 2024)
Poverty remains a significant issue in North Sumatra, with the percentage of poor people in urban areas reaching 4.93% in 2022 and 4.67% in the first semester of 2023. This phenomenon is influenced by various factors, including inflation, unemployment rate, per capita income, and Human Development Index (HDI). This study aims to examine the effects of these factors on poverty levels, measured by the Poverty Severity Index (PSI), and to evaluate the role of zakat as a moderating variable in the relationship between economic factors and poverty. The study findings reveal that inflation and per capita income have a significant negative impact on PSI, meaning that increases in inflation and per capita income are associated with a reduction in poverty severity. Conversely, HDI shows a significant positive impact on PSI, indicating that higher HDI in some regions can actually increase poverty severity. The unemployment rate does not show a significant effect on PSI. The role of zakat as a moderating variable was also found to be significant. Zakat weakens the negative effect of inflation on poverty and strengthens the negative effect of per capita income on poverty. However, zakat does not moderate the relationship between HDI and unemployment rate with poverty. This study provides insights into how zakat can function as a tool to enhance the effectiveness of economic factors in reducing poverty in North Sumatra.